Basic concept of healthy aging - Chalise, Hom Nath (Journal of Patan Academy of Health Sciences, 2022)
Rapid population aging is a characteristic of 21st century, regardless of a nation’s level of development. An ageing global population results burden in medical and social demographic problem worldwide. Addressing this problem is the highest priority for the care of the ageing population worldwide. Healthy ageing is an individual lived experience that is influenced by healthy behaviours over the course of a lifetime. This includes a person’s ability to: meet their basic needs; learn, grow and make decisions; be mobile; build and maintain relationships; and contribute to society. For the promotion of healthy aging, healthy life style is important. A healthy lifestyle for older adults includes: healthy eating, regular physical activity, staying at a healthy weight, improving mental health, social participation, regular health checkups and health screening, no smoking and taking steps to prevent falls.